2020
DOI: 10.1166/jmihi.2020.2947
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Segmentation and Modeling of Lung Cancer Images Scanned Continuously by Computed Tomography Based on Materiaise's Interactive Medical Image Control System

Abstract: The purpose of this study is to explore the value of CT (computed tomography) continuous scanning by MIMICS (Materiaise's interactive medical image control system) in segmentation modeling of lung cancer images and to analyze the process of building a three-dimensional finite element model of lung cancer quickly and accurately. In this study, MIMICS software is used to conduct data collection of routine CT continuous image for 12 patients diagnosed with lung cancer, and a database is established. The image is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Hongtao et al (2020) [ 27 ] demonstrated the application of segmentation and modeling of lung cancer using 3D renderings created from CT images. The segmentation performed using MIMICS17.0 software and demonstrated high precision; however, due to software limitations, the exact coordinates of tumor location cannot yet be exported.…”
Section: Introductionmentioning
confidence: 99%
“…Hongtao et al (2020) [ 27 ] demonstrated the application of segmentation and modeling of lung cancer using 3D renderings created from CT images. The segmentation performed using MIMICS17.0 software and demonstrated high precision; however, due to software limitations, the exact coordinates of tumor location cannot yet be exported.…”
Section: Introductionmentioning
confidence: 99%